Unresolved issues and current concepts in management of primary glomerulonephritis - Dash, Suresh Chandra (Ann Saudi Med, 2005)
The successful treatment of primary glomerulonephritis (GN) presenting with nephrotic syndrome in adults depends heavily on an accurate diagnosis. A successful diagnosis depends on a correct approach, combining light microscopy, immunofluorescence, and other special staining of renal biopsy material examined by a trained nephropathologist. A good clinical history and serological tests easily rule out possible secondary causes (for example, infection, autoimmune, metabolic or toxic) in most cases. Unfortunately, these procedures are not put into practice in most cases in developing countries, resulting in missed diagnosis and unnecessary steroid and immunosuppressant therapy with its inherent morbidity. Following the emergence of IgA and IgM nephropathies as very common forms of glomerular disorders in some countries, immunofluorescence has become absolutely necessary for their diagnosis. Moreover, a recent meta-analysis has defined different treatment protocols for minimal change nephropathy, focal segmental glomerulosclerosis, membranous nephropathy, and IgA nephropathy for a better outcome. This article emphasizes and elaborates on these issues for proper management of primary GN.